Subsequent Development of Desmoid Tumor after a Resected Gastrointestinal Stromal Tumor - Areen Abdulelah Murshid; Hatim Q. Al-Maghraby (Case Reports in Pathology)
Desmoid tumors (deep fibromatosis) of the mesentery are rare mesenchymal tumors. They are often misdiagnosed, especially with a previous history of resection for gastrointestinal stromal tumor (GIST). Immunohistochemistry can help differentiate between these two tumors. In this article, we present a case we had encountered: a Desmoid tumor developing in a patient with a history of GIST 3 years ago. It is the first case of GIST with subsequent development of Desmoid tumor to be reported in Saudi Arabia. We discuss the two entities of Desmoid tumor and GIST by comparing their definitions, clinical presentations, histological features, immunohistochemistry stains, molecular pathogenesis, prognosis, and treatment. We also discuss the relationship between GIST and the subsequent development of Desmoid tumors and compare our case with case reports in literature.